2016
DOI: 10.1016/j.neuroimage.2015.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Morphological maturation of the mouse brain: An in vivo MRI and histology investigation

Abstract: With the wide access to studies of selected gene expressions in transgenic animals, mice have become the dominant species as cerebral disease models. Many of these studies are performed on animals of not more than eight weeks, declared as adult animals. Based on the earlier reports that full brain maturation requires at least three months in rats, there is a clear need to discern the corresponding minimal animal age to provide an "adult brain" in mice in order to avoid modulation of disease progression/therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
114
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(124 citation statements)
references
References 30 publications
9
114
1
Order By: Relevance
“…First, most gray matter regions reach their final volume within the first 8 postnatal weeks (Hammelrath et al 2015). Second, there is an initial decrease in T 2 from 3 to 8 weeks postnatal, after which T 2 steadily increases up to 24 weeks of age (Hammelrath et al 2015). Taken together, our findings of widespread decreases in T 2 in POL offspring at 12 weeks postnatal suggest a delay in the normal process of mouse brain maturation following maternal immune activation.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…First, most gray matter regions reach their final volume within the first 8 postnatal weeks (Hammelrath et al 2015). Second, there is an initial decrease in T 2 from 3 to 8 weeks postnatal, after which T 2 steadily increases up to 24 weeks of age (Hammelrath et al 2015). Taken together, our findings of widespread decreases in T 2 in POL offspring at 12 weeks postnatal suggest a delay in the normal process of mouse brain maturation following maternal immune activation.…”
Section: Discussionmentioning
confidence: 55%
“…Although longitudinal in vivo MRI studies will be helpful to clarify this, we have recently shown that prenatal immune activation on GD 17 in mice leads to an "immature" cortical GABAergic network in early adulthood, supporting a "delayed maturation" hypothesis (Richetto et al, 2014). Importantly, rats and mice show differential timescales of brain maturation, thus these findings may not translate precisely across species (Mengler et al 2014;Hammelrath et al 2015) How do these macroscale findings relate to those at the transcriptional level, particularly with respect to myelination? Our postmortem immunohistochemistry analysis of the mPFC is in line with the gene expression data, with no change in MBP, but a decrease in MOBP.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, this finding echoes our earlier finding of the rate of myelination being fastest at 70% depth between the pial surface and the grey/white matter boundary, and the relationship between rate of cortical thinning and rate of myelination being strongest at this depth (Whitaker, Vértes et al 2016). We have previously suggested a link of these changes to histological evidence of greatest rates of myelination at similar cortical depths in rodents (Mengler et al 2014; Tomassy et al 2014; Hammelrath et al 2016). …”
Section: Discussionmentioning
confidence: 94%
“…In rodents, there is histological evidence for increasing intracortical myelination during adolescence, especially at the deeper cytoarchitectonic layers of cortex (V and VI) (18,19). At a cellular…”
mentioning
confidence: 99%